Analysis of the Fee-to-Tax Reform on Water Resources in China - Chen, Zi-Rui; Yuan, Yuan; Xiao, Xu (Frontiers in Energy Research, 2021)
The Resource Tax Law was officially implemented on September 1, 2020, in China. This law presents the “Fee-to-Tax” reform of water resources. This article compares the effects of the “Fee-to-Tax” reform under asymmetric duopoly conditions with perfect information. The mechanisms of the two policies are different when all firms simultaneously respond to water resources: the water resource fee affects output by reducing market size, while the water resource tax reduces output by amplifying the weighted cost difference effects between companies. Water resource taxes work better than fees for eliminating backward production capacity. A comparison of the situation when companies respond sequentially is also carried out. When a low-cost firm is in the leading position, the collection of fees actually reduces the output difference, whereas the tax improves it. When a high-cost firm acts as a leader, the effects depend on the cost difference. When the cost difference between firms is small, the first-move advantage of high-cost firms dominates the cost advantages of low-cost firms. Therefore, a higher tax rate yields a smaller output difference. When cost differences are relatively larger, the cost advantage of low-cost firms dominates the first-move advantage of high-cost firms. As the operational cost for reducing water consumption increases, the reduced water consumption first increases and then decreases.